Penilaian kurikulum Program Ijazah Sarjana Muda Perguruan (PISMP) Pendidikan Islam di Institut Pendidikan Guru Malaysia - Mohd Zailani, Ismail (2019)
Audit reports found some weakness aspects in the program of Bachelor Degree in Islamic Education (PISMP). This is in line with the suggestions by evaluation experts which indicate the need for further investigation regarding this issue. Therefore, the study aims to evaluate the Bachelor Degree in Islamic Education (PISMP) program at Malaysian Institute of Teachers Education based on the Context-Input-Process-Product (CIPP) Model. The focus of the study is on the dimensions of context, input, process, and product, as well as the determination of product differences by zone, and identifying the influence of context, input, and process dimensions toward the product of PISMP’s Islamic Education program. A Mixed Method Research (MMR) using questionnaire, interview, document analysis, and experts’ checklists were applied. Quantitative data was gathered through questionnaires from 305 teacher trainees, 96 lecturers and seven evaluation experts. Meanwhile, qualitative data was obtained through the interviews of 11 respondents, and document analysis. Data analysis was done using IBM SPSS version 20.0. Descriptive findings show some aspects of context, input, and process are good, but still require improvements. MANOVA test found a significant difference in knowledge of curriculum content based on zones, but not in pedagogical knowledge, establishment of positive attitudes, transferability of skills, and impact of program satisfaction from product dimensions. Multiple regression test recorded 70.6% of product outcomes were influenced by the predictors of 21st century pedagogy, coursework/project implementation, professional practices, and curriculum content suitability. Hence, this study has sigifican implications to the whole IPG in which the 21st century pedagogical practices, practicum or professional practices, coursework/project alignment and appropriate curriculum contents are vital in producing competent and professional teacher trainees. Moreover, specific Program Learning Outcomes (PLO) for PISMP specialization in Islamic Education and appropriate Program Education Objectives (PEO) are also catalysts for the effectiveness of program implementation.